A Narrative Review: How to Optimize Program Keluarga Harapan in Addressing Nutritional Issues in Indonesia - Nihayatul Putri; Annisa Alifaradila Rachmayanti; Yuga Putri Pramesti (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2024)
Indonesia's Conditional Cash Transfer (CCT) program, Program Keluarga Harapan (PKH), aims to alleviate poverty and improve access to essential services. However, its effectiveness in addressing the root causes of poverty, malnutrition, and stunting has been subject to criticism, as it primarily focuses on alleviating immediate financial constraints. This literature review critically analyses the existing research on the PKH program's effectiveness in addressing nutritional issues in Indonesia. Literature selection, data extraction, and analysis were employed. Based on the literature search strategy and criteria, four key papers were collected. These studies indicated that CCT/PKH could not stand alone in tackling nutritional problems. There are several supporting components that should be taken into consideration in implementing the programme, including 1) the requirement of a standardized healthcare facility; 2) focusing on quality in small numbers rather than covering a wide scale with minimum impact; 3) supplementing CCT/PKH with health education and promotion programme; and 4) improving access to health and nutritional services. A whole-system approach, involving various stakeholders and integrating targeted interventions, has the potential to break the intergenerational cycle of poverty and ensure a healthier future for all Indonesians.